Effect of UMMB Supplementation on Metabolic and Oxidative Parameters in Rambouillet Cross Sheep during Peripartum Period - Singh, A P; Singh, R; Bhat, A M; Tikoo, A; Pathak, A K (Indian Journal of Animal Nutrition, 2019)
The study was conducted to assess the effect of supplementing urea molasses multi-nutrient blocks on body weight gain, hemato-biochemical parameters, mineral status and oxidative stress in crossbred Rambouillet sheep in advanced pregnancy. The animals were categorized into 2 group’s viz. group-A (control) and group-B (UMMB supplemented @ 50gm/day) with 6 animals in each group. Along with body weight, blood samples were collected at 4 weeks and 1 week before lambing, followed by 1, 4 and 8 weeks after lambing. The average body weight increase of UMMB supplemented animals was 40% compared with 21% among control group animals. In treatment group, there was significant increase (P